The Box Spread Arbitrage Conditions: Theory, Tests, and Investment Strategies - Ronn, Aimee Gerbarg; Ronn, Ehud I. (Review of Financial Studies, 1989)
This paper develops and tests arbitrage bounds for a combination of two option spread positions known as a box spread. This strategy involves the simultaneous use of four options and creates a position that is equivalent to riskless lending. The no-arbitrage conditions are compared to existing arbitrage bounds and are tested using Chicago Board Options Exchange data.